Repair slurry and repair method for graphite crucible

By using two-component repair slurry to fill and cure the damaged parts of the graphite crucible and perform surface coating and curing, the scrapping problem of graphite crucible due to cracks or damage is solved, extending the service life, reducing costs, and in line with environmental protection concepts.

CN119591424AInactive Publication Date: 2025-03-11HUNAN HONGYU CARBON NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411748995.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the use of the graphite crucible, due to physical collision, friction and high-temperature smelting, its strength is reduced, its structure is loose, and it cannot be used. It must be scrapped, which increases the cost of use.

Method used

A two-component repair slurry is provided, including structural repair slurry and surface repair slurry. The damaged parts are filled and solidified by structural repair slurry, and then surface coating and curing is used to achieve the repair of graphite crucibles.

Benefits of technology

It extends the service life of graphite crucibles, reduces maintenance costs and replacement frequency, and the surface of the repaired graphite crucible is smooth, complies with the quality requirements of industrial production, reduces the production of industrial waste, and conforms to the environmental protection concept of sustainable development.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a repair slurry for a graphite crucible, the repair slurry comprises a structure repair slurry and a surface layer repair slurry, and the two slurries comprise a matrix, a repair agent, a binder and a solvent with different proportional relations; the base body and the solvent of the structure repairing slurry are the same as those of the surface layer repairing slurry, and the repairing agent and the structure repairing slurry have component difference; the corresponding repairing method of the graphite crucible comprises the following steps: firstly cleaning the damaged part of the graphite crucible, then filling the damaged part with the structure repairing slurry, naturally or heating and curing, then coating the surface with the surface layer repairing slurry, heating and curing, and then grinding and polishing to the required size and shape. The use performance of the graphite crucible is ensured, the damaged part of the graphite crucible can be effectively repaired, the service life of the graphite crucible is remarkably prolonged, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crucible repair devices, and in particular to a repair slurry and a repair method for a graphite crucible. Background Art

[0002] Graphite crucible, also known as molten copper bag, molten copper, etc., refers to a type of heat treatment container made of graphite, clay, silica and wax stone as raw materials. It has good thermal conductivity and high temperature resistance. During high-temperature use, its thermal expansion coefficient is small, and it has good resistance to rapid heating, rapid cooling, acid and alkali environment. It is widely used in the smelting of alloy tool steel and the smelting of non-ferrous metals and their alloys.

[0003] There will be certain losses in the actual use of graphite crucibles. This loss includes two categories. One is the surface damage caused by physical collision and friction during logistics transportation, storage, transportation, installation and other links. The other is the high-temperature smelting process. Due to its own material properties and thermal stress, chemical corrosion and other reasons, the strength of the graphite crucible will be reduced and the structure will be loose, which will lead to cracks or damage to the graphite crucible.

[0004] Normally, once a graphite crucible is cracked or damaged, it cannot be used any more and must be scrapped and replaced with a new crucible. This process results in a continuously high cost of using the graphite crucible. In order to extend the service life of the graphite crucible, repairing the cracked or damaged parts and recycling the graphite parts is a key strategy to improve the durability of the graphite crucible, which is extremely important for reducing production costs. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a repair slurry and a repair method for a graphite crucible to solve the shortcomings of the above-mentioned background technology.

[0006] The technical problem solved by the present invention is achieved by adopting the following technical solutions:

[0007] The present invention firstly discloses a repair slurry for a graphite crucible, wherein the repair slurry is a two-component repair slurry, including a structural repair slurry and a surface repair slurry;

[0008] The structural repair slurry comprises: 50 to 60 parts by mass of a base, 10 to 15 parts by mass of a repair agent, 3 to 5 parts by mass of a binder and an appropriate amount of a solvent;

[0009] The matrix is ​​a composition of graphite fine powder, electrode powder and mullite powder, the mass percentages of the three being 60% to 70%, 20% to 30% and 10% to 15% respectively;

[0010] The repair agent is a composition of coke powder, graphite powder and asphalt powder, the mass percentages of the three being 40% to 50%, 30% to 40% and 20% to 30% respectively;

[0011] The binder is a bisphenol A epoxy resin with an epoxy value of 0.4 to 0.6 mol / kg;

[0012] The solvent is one or a mixture of xylene, acetone and ethyl acetate.

[0013] The surface repair slurry comprises: 40 to 50 parts by mass of a base, 15 to 20 parts by mass of a repair agent, 5 to 10 parts by mass of a binder and an appropriate amount of a solvent;

[0014] The matrix is ​​a composition of graphite fine powder, electrode powder and mullite powder, the mass percentages of the three being 60% to 70%, 20% to 30% and 10% to 15% respectively;

[0015] The repair agent comprises a composition of coke powder, graphite powder, asphalt powder, silicon carbide and aluminum oxide, wherein the mass percentages of the aforementioned components are 30% to 40%, 20% to 30%, 15% to 25%, 10% to 15% and 5% to 10% respectively;

[0016] The binder is one or a combination of polyacrylonitrile and polyacrylate;

[0017] The solvent is one or a mixture of xylene, acetone and ethyl acetate.

[0018] As a further limitation, the structural repair slurry and the surface repair slurry also include a curing agent and a dispersant; the curing agent is meta-phenylenediamine; and the dispersant is polyvinyl alcohol.

[0019] As a further limitation, the graphite fine particles used in the raw materials are graphite crucible crushed materials and scraps generated during the production and use process of carbon enterprises and have not been used in the furnace.

[0020] As a further limitation, the coke powder used in the raw material is a composition of calcined coke, needle coke and anthracite powder in a mass ratio of 2:2:1.

[0021] As a further limitation, both the structural repair slurry and the surface repair slurry are modulated into slurries with different viscosities using solvents; the viscosity of the structural repair slurry after modulation is 1000-1500 mPa·s, while the viscosity of the surface repair slurry is 500-1000 mPa·s.

[0022] As a further limitation, the particle size range of the coke powder used to prepare the repair agent is 80-200 μm, and the particle size range of the mullite powder, graphite powder and asphalt powder is 10-30 μm.

[0023] As a further limitation, the corresponding structural repair slurry and surface repair slurry are ready to use, and the preparation steps of the structural repair slurry and the surface repair slurry are as follows:

[0024] First, the base material is dry-mixed, and the stirring speed of the equipment is maintained at 100-150 r / min during dry mixing, and the duration is 10-15 minutes. The repair agent is added and continued to be stirred, and the stirring speed of the equipment is maintained at 150-200 r / min, and the duration is 15-20 minutes to obtain;

[0025] Add the binder into the solvent and keep the stirring speed at 600-800 r / min, and continue stirring for 5-10 minutes to obtain;

[0026] The mixture A is slowly and continuously added to the mixture B and stirred at a speed of 1000-1500 r / min. The stirring is continued until a uniform mixture is formed and stored in a container to obtain the corresponding structural repair slurry and surface repair slurry.

[0027] The present invention also discloses a method for repairing a graphite crucible, which specifically comprises the following steps:

[0028] S1. Clean the damaged part of the graphite crucible to remove loose graphite particles and oil stains from the damaged part, and then polish the inner and outer surfaces of the graphite crucible to remove the film layer and oxide layer;

[0029] S2. Fill the damaged part of the graphite crucible with the structural repair slurry to ensure that it is densely filled, and use a scraper to keep the slurry and the surface of the graphite crucible flat. Turn the repaired graphite crucible upside down and place it at room temperature for natural curing or by heating for curing;

[0030] S3. After the structural repair slurry is solidified, the surface repair slurry is used to coat the filled surface. After coating, it is cured by heating. After curing, the graphite crucible is ground and polished as necessary to meet the processing size and shape requirements.

[0031] As a further limitation, when filling and repairing the damaged part of the graphite crucible with the structural repair slurry, the inner and outer molds can be nested, and the specific operation is as follows:

[0032] When the damaged part of the graphite crucible is on the outside, a structural outer mold and the outside of the graphite crucible are set, and then a structural repair slurry is injected into the gap between the graphite crucible and the structural outer mold by means of supercharged injection to perform filling and repair;

[0033] When the damaged part of the graphite crucible is on the inner side, a structural inner mold and the inner side of the graphite crucible are set, and then a structural repair slurry is injected into the gap between the graphite crucible and the structural inner mold by means of boost injection to perform filling and repairing;

[0034] When the damaged part of the graphite crucible is a through structure, a structural outer mold and a structural outer mold are set at the same time, and then the structural repair slurry is filled and repaired by pressurized injection on both sides of the graphite crucible at the same time.

[0035] As a further limitation, in step S3, the graphite crucible after grinding and polishing is directly subjected to coating forming, and the coating forming method is a plasma spraying method.

[0036] Beneficial effects: The repair slurry for graphite crucible of the present invention has good bonding performance and high temperature resistance, and can ensure that the repaired graphite crucible maintains structural integrity and stability during high-temperature smelting; and the corresponding repair method is simple to operate, easy to master, suitable for on-site rapid repair, and can effectively repair the damaged parts of the graphite crucible, extend its service life, and reduce the cost caused by frequent replacement of the crucible;

[0037] By using the above-mentioned repair slurry and method, the maintenance cost and replacement frequency of graphite crucibles can be significantly reduced. The surface of the repaired graphite crucible is smooth, which meets the requirements of industrial production for the surface quality of the crucible, and saves a lot of maintenance costs and production costs for enterprises. At the same time, the promotion and use of this repair technology will also help reduce the generation of industrial waste, which is in line with the current environmental protection concept of sustainable development.

[0038] At the same time, the repair slurry and the repair method of the present invention are not only applicable to graphite crucibles, but can also be extended to the repair of other graphite products, and have broad application prospects. DETAILED DESCRIPTION

[0039] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0040] In the following embodiments, it will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as the meaning in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless defined as herein.

[0041] In Example 1, the structural repair slurry and the surface repair slurry in the repair slurry for the graphite crucible are prepared by the following method:

[0042] First prepare the raw materials:

[0043] The unused graphite crucible crushed materials and scraps produced by carbon enterprises are selected as the raw materials of graphite fine crushing materials, which are mechanically crushed and pulverized to obtain powder with a particle size of less than 1mm, that is, graphite fine crushing materials. At the same time, calcined coke, needle coke and anthracite powder with a particle size range of 80-200μm are selected and mixed in a mass ratio of 2:2:1 to obtain coke powder.

[0044] The electrode crushed materials are screened to obtain electrode crushed materials with a particle size less than 1 mm.

[0045] Mullite powder, graphite powder and asphalt powder can be purchased directly from the market with a particle size of less than 30 μm. Silicon carbide and alumina can be purchased directly from the market with a particle size of less than 500 nm. No further processing is required.

[0046] Then, a structural repair slurry was prepared. When preparing the structural repair slurry, 600 g of graphite fine powder, 200 g of electrode powder and 120 g of mullite powder were first put into a dry mixing device for mixing. During mixing, the stirring speed of the dry mixing device was controlled to be 120 r / min for 12 minutes, and then 130 g of coke powder, 100 g of graphite powder and 70 g of asphalt powder were added and continued to stir. The stirring speed of the equipment was kept at 180 r / min for 18 minutes to obtain a mixture A.

[0047] Next, in another stirring container, 150 g of bisphenol A epoxy resin (epoxy value: 0.43 mol / kg) was added to 1000 g of xylene, and the stirring speed was maintained at 700 r / min. The stirring was continued for 7 minutes to obtain a mixture B.

[0048] The mixture A is slowly and continuously added into the mixture B, and the mixture is stirred at a speed of 1200 r / min until a uniform mixture is formed, thereby obtaining a structural repair slurry.

[0049] The preparation process of the surface repair slurry is similar to that of the structural repair slurry, but the total mass of graphite fine particles, electrode fragments and mullite powder in mixture A is 500g, the total mass of coke powder, graphite powder and asphalt powder is 150g, and the bisphenol A epoxy resin in mixture B is replaced by polyacrylate with a mass of 180g, and the mass of the solvent xylene is 1200g.

[0050] The process parameters are controlled to be consistent with the process parameters during the preparation of the structure repair slurry, and finally the surface repair slurry is obtained.

[0051] In other embodiments including Embodiment 1, it is necessary to ensure uniform mixing through dry mixing and wet mixing, and the viscosity of the final slurry meets the requirements, and the corresponding structural repair slurry is 1000-1500mPa·s, and the surface repair slurry is 500-1000mPa·s.

[0052] In Example 2: the structural repair slurry and the surface repair slurry in the repair slurry for graphite crucible are different only in the raw material components. The specific preparation method is the same as that in Example 1, but the raw material components are adjusted.

[0053] In Example 2, the selection of graphite fine powder is the same as that in Example 1, but the preparation method of coke powder is slightly different. Calcined coke, needle coke, and anthracite powder with a particle size range of 50 to 150 μm are selected and mixed in a mass ratio of 1:1:1 to obtain coke powder. The screening and particle size selection of electrode crushed material are also the same as those in Example 1.

[0054] When preparing the structural repair slurry, the composition of mixture A was adjusted to 550 g of graphite fine powder, 250 g of electrode powder and 150 g of mullite powder, and the total mass of coke powder, graphite powder and asphalt powder was adjusted to 140 g, 110 g and 80 g. The mass of bisphenol A epoxy resin in mixture B remained unchanged, but the mass of solvent xylene was adjusted to 1100 g.

[0055] During the preparation of the surface repair slurry, the composition of mixture A was adjusted to 450g of graphite fines, 250g of electrode crushed materials and 150g of mullite powder, and the total mass of coke powder, graphite powder and asphalt powder was adjusted to 160g, 120g and 90g. The mass of polyacrylate in mixture B was adjusted to 190g, and the mass of solvent xylene was adjusted to 1300g.

[0056] In Example 3, the performance of the repair slurry was further optimized by adjusting the particle size range and mixing ratio of the raw materials in order to achieve a better repair effect. When preparing the structural repair slurry, the particle sizes of the graphite fines, electrode crushed materials and mullite powder in mixture A were adjusted to less than 0.5 mm, and the particle sizes of the coke powder, graphite powder and asphalt powder were adjusted to less than 20 μm. The mass of bisphenol A epoxy resin in mixture B was adjusted to 160 g, and the mass of the solvent xylene was adjusted to 900 g.

[0057] In the preparation process of the surface repair slurry, the particle sizes of graphite fine particles, electrode particles and mullite powder in mixture A are all adjusted to less than 0.5 mm, and the particle sizes of coke powder, graphite powder and asphalt powder are adjusted to less than 15 μm. Polyacrylonitrile is selected as the binder in mixture B, and the mass is adjusted to 200 g, and the mass of the solvent xylene is adjusted to 1400 g.

[0058] The group structure repair slurry and surface layer repair slurry prepared in the above implementation are used as raw materials to carry out the filling and repair operation of the broken graphite crucible. The specific operation steps are as follows:

[0059] S1. First, clean the damaged parts of the graphite crucible thoroughly, use high-pressure air to blow away loose graphite particles and oil stains, and then use sandpaper to polish the inner and outer surfaces of the graphite crucible to remove the oxide layer and film layer on the surface.

[0060] S2. Evaluate the damaged parts of the graphite crucible and select the appropriate repair slurry for filling according to the degree of damage. For surface cracks, only use the surface repair slurry for surface repair. For cracks or damage, first use the structural repair slurry to fill, and then use the surface repair slurry for surface coating after curing;

[0061] When repairing, fill the damaged part of the graphite crucible with structural repair slurry, use a scraper to ensure that the slurry is densely filled, and use the scraper to keep the slurry and the surface of the graphite crucible flat. After filling, turn the graphite crucible upside down and place it at room temperature to cure naturally, or heat cure it at a temperature range of 60-100℃ to accelerate the curing process.

[0062] S3. After curing, check the graphite crucible to ensure that there are no defects in the repaired part. If necessary, secondary filling and curing can be performed until the repaired part reaches satisfactory strength and appearance.

[0063] S4. Apply the surface repair slurry evenly to the surface of the crucible body that has been filled and repaired with the structural repair slurry and other areas that need to be repaired, ensuring that the coating is evenly covered, and use a scraper or similar tool to ensure that the slurry is flat and free of bubbles.

[0064] S5. After the coating is completed, the graphite crucible is placed at a temperature of 100-150°C for thermal curing to ensure that the surface repair slurry is cured and formed.

[0065] S6. After curing is completed, the repaired area is polished to ensure a smooth transition with the surrounding unrepaired area. Finally, the entire graphite crucible is thoroughly cleaned and inspected to ensure that there is no residual repair material and to confirm that the repair effect meets the requirements for use.

[0066] The broken crucible is repaired by the above three embodiments, and the electrode fragments play the role of aggregate; the coke powder mainly plays the role of mixing the electrode fragments, filling the gaps between the aggregate particles, and enhancing the density; the asphalt powder mainly plays the role of bonding under high temperature conditions. In the selection of the repairing agent, the composition of coke powder, graphite powder, asphalt powder, silicon carbide, and aluminum oxide is carefully proportioned to ensure that the repairing agent can form a uniform and stable composite material after mixing with the matrix. The composition of calcined coke, needle coke, and anthracite powder of coke powder not only provides the necessary carbon source, but also enhances the binding force and thermal stability of the repairing agent through a specific mass ratio.

[0067] As a key component in the slurry, the binder ensures that the repair material forms a strong adhesion layer on the surface of the graphite crucible. The use of polyacrylonitrile and polyacrylate, due to their excellent bonding properties and chemical corrosion resistance, enables the repaired graphite crucible to maintain good structural integrity in high temperature and chemical corrosion environments.

[0068] As for the solvent, the use of xylene, acetone and ethyl acetate alone or in combination can not only provide good dissolving properties, but also effectively control the viscosity of the slurry during the construction process, ensuring that the repair material can be evenly coated on the damaged part of the graphite crucible.

[0069] The damaged crucible still has good mechanical strength and high temperature resistance after repair. In the above repair process, the repaired graphite crucible was placed in a smelting furnace for actual smelting test. The repair effect was evaluated by comparing the thermal expansion coefficient, high temperature resistance and service life of the graphite crucible before and after the repair. The results show that the repaired graphite crucible can meet the use requirements in industrial production in all performance indicators.

[0070] In actual application, the repaired crucible can not only withstand chemical reactions at high temperatures, but also restore its original stability in structure. In addition, there is good adhesion between the repair material and the base material of the graphite crucible, ensuring the long-term durability of the repaired part. The repaired graphite crucible can be used in the smelting process of various metals, including but not limited to the smelting of aluminum, copper, iron and other metals. Due to the corrosion resistance of the repair material, the repaired crucible also shows excellent durability when handling molten metal containing corrosive substances.

[0071] In another embodiment, in order to optimize the repairing efficiency and the repairing effect, the repairing operation of the crucible can be assisted by setting a structural outer mold and a structural outer mold. The specific operation method is as follows:

[0072] When the damaged part of the graphite crucible is on the outside, first prepare a structural outer mold that matches the shape of the damaged part of the graphite crucible, and then fit the damaged part of the graphite crucible closely to the structural outer mold to ensure that there is no obvious gap between the two. Next, inject the structural repair slurry into the gap between the graphite crucible and the structural outer mold by pressurized injection, and use the shape of the outer mold to guide the slurry to evenly fill the damaged part.

[0073] During the slurry injection process, a certain pressure should be maintained to ensure that the slurry can fully penetrate every corner of the damaged part, and with the help of the structural outer mold, the slurry can form a repair layer that matches the original shape of the graphite crucible. After the slurry injection is completed, the graphite crucible is placed at room temperature for natural curing or heat-cured at an appropriate temperature to accelerate the curing process. After the structural repair slurry is completely cured, the structural outer mold is removed, and the repaired part is ground and polished to ensure a smooth transition between the repaired part and other parts of the graphite crucible.

[0074] For the damaged part inside the graphite crucible, a similar method can be used, but a structural inner mold is needed to assist the repair work. First, prepare a structural inner mold that matches the shape of the damaged part inside the graphite crucible and place it on the damaged part inside the graphite crucible. Then, inject the structural repair slurry into the gap between the graphite crucible and the structural inner mold by pressurized injection, ensuring that the slurry evenly fills the damaged part. After curing, remove the structural inner mold and grind and polish the repaired part to achieve the same surface quality as other parts of the graphite crucible.

[0075] For the penetrating damaged parts of the graphite crucible, the structural outer mold and the structural inner mold can be used for repair at the same time. First, prepare the structural outer mold and the structural inner mold that match the shape of the damaged parts on the outside and inside of the graphite crucible, and place them on the damaged parts on the outside and inside of the graphite crucible respectively. Then, by means of pressurized injection, the structural repair slurry is injected into the gap from both the inside and outside of the graphite crucible to ensure that the slurry evenly fills the damaged part. After curing is completed, remove the structural outer mold and the structural inner mold, and grind and polish the repaired part to ensure a smooth transition between the repaired part and other parts of the graphite crucible.

[0076] In order to further improve the repair effect, the plasma spraying method is used to coat the ground and polished graphite crucible. The specific operation is:

[0077] A plasma spray coating with a thickness of about 0.1 mm is applied on the surface of the graphite crucible. The spraying material is alumina. During the spraying process, the spraying temperature is controlled between 800 and 1000°C and the spraying speed is 100 mm / s. After the spraying is completed, a uniform and dense alumina coating is formed on the surface of the graphite crucible, which effectively improves the corrosion resistance and high temperature resistance of the graphite crucible.

[0078] Through the above embodiments, the repair slurry and the repair method of the present invention show good repair effect and stability in practical applications, can significantly extend the service life of the graphite crucible, reduce production costs, and have broad application prospects.

[0079] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A repair slurry for a graphite crucible, characterized in that: The repair slurry is a two-component repair slurry, including a structural repair slurry and a surface repair slurry; The structural repair slurry comprises: 50 to 60 parts by mass of a base, 10 to 15 parts by mass of a repair agent, 3 to 5 parts by mass of a binder and an appropriate amount of a solvent; The matrix is ​​a composition of graphite fine powder, electrode powder and mullite powder, the mass percentages of the three being 60% to 70%, 20% to 30% and 10% to 15% respectively; The repair agent is a composition of coke powder, graphite powder and asphalt powder, the mass percentages of the three being 40% to 50%, 30% to 40% and 20% to 30% respectively; The binder is a bisphenol A epoxy resin with an epoxy value of 0.4 to 0.6 mol / kg; The solvent is one or a mixture of xylene, acetone and ethyl acetate; The surface repair slurry comprises: 40 to 50 parts by mass of a base, 15 to 20 parts by mass of a repair agent, 5 to 10 parts by mass of a binder and an appropriate amount of a solvent; The matrix is ​​a composition of graphite fine powder, electrode powder and mullite powder, the mass percentages of the three being 60% to 70%, 20% to 30% and 10% to 15% respectively; The repair agent comprises a composition of coke powder, graphite powder, asphalt powder, silicon carbide and aluminum oxide, wherein the mass percentages of the aforementioned components are 30% to 40%, 20% to 30%, 15% to 25%, 10% to 15% and 5% to 10% respectively; The binder is one or a combination of polyacrylonitrile and polyacrylate; The solvent is one or a mixture of xylene, acetone and ethyl acetate.

2. The repair slurry for graphite crucible according to claim 1, characterized in that: The structural repair slurry and the surface repair slurry also include a curing agent and a dispersing agent; the curing agent is meta-phenylenediamine; and the dispersing agent is polyvinyl alcohol.

3. The repair slurry for graphite crucible according to claim 1, characterized in that: The graphite fine particles used in the raw materials are graphite crucible crushed materials and scraps produced during the production and use of carbon enterprises and not put into the furnace for use; the coke powder used is a composition of calcined coke, needle coke and anthracite powder in a mass ratio of 2:2:

1.

4. The repair slurry for graphite crucible according to claim 1, characterized in that: Both the structural repair slurry and the surface repair slurry are prepared into slurries with different viscosities using solvents; The viscosity of the structure repair slurry after modulation is 1000-1500 mPa·s, while the viscosity of the surface repair slurry is 500-1000 mPa·s.

5. The repair slurry for graphite crucible according to claim 1, characterized in that: The particle size range of the coke powder used for preparing the repair agent is 80-200 μm, and the particle size range of the mullite powder, graphite powder and asphalt powder is 10-30 μm.

6. The repair slurry for graphite crucible according to claim 1, characterized in that: The corresponding structural repair slurry and surface repair slurry are ready to use. The preparation steps of the structural repair slurry and surface repair slurry are as follows: First, the base material is dry-mixed, and the stirring speed of the equipment is maintained at 100-150 r / min during dry mixing, and the duration is 10-15 minutes. The repair agent is added and continued to be stirred, and the stirring speed of the equipment is maintained at 150-200 r / min, and the duration is 15-20 minutes to obtain; Add the binder into the solvent and keep the stirring speed at 600-800 r / min, and continue stirring for 5-10 minutes to obtain; The mixture A is slowly and continuously added to the mixture B and stirred at a speed of 1000-1500 r / min. The stirring is continued until a uniform mixture is formed and stored in a container to obtain the corresponding structural repair slurry and surface repair slurry.

7. A method for repairing a graphite crucible, characterized in that: The repairing operation of a damaged graphite crucible is performed by using the repair slurry according to any one of claims 1 to 6 as a raw material, which specifically includes the following steps: S1. Clean the damaged part of the graphite crucible to remove loose graphite particles and oil stains from the damaged part, and then polish the inner and outer surfaces of the graphite crucible to remove the film layer and oxide layer; S2. Fill the damaged part of the graphite crucible with the structural repair slurry to ensure that it is densely filled, and use a scraper to keep the slurry and the surface of the graphite crucible flat. Turn the repaired graphite crucible upside down and place it at room temperature for natural curing or by heating for curing; S3. After the structural repair slurry is solidified, the surface repair slurry is used to coat the filled surface. After coating, it is cured by heating. After curing, the graphite crucible is ground and polished as necessary to meet the processing size and shape requirements.

8. The repair method for a graphite crucible according to claim 1, characterized in that: When using the structural repair slurry to fill and repair the damaged parts of the graphite crucible, the inner and outer molds can be nested. The specific operation is as follows: When the damaged part of the graphite crucible is on the outside, a structural outer mold and the outside of the graphite crucible are set, and then a structural repair slurry is injected into the gap between the graphite crucible and the structural outer mold by means of supercharged injection to perform filling and repair; When the damaged part of the graphite crucible is on the inner side, a structural inner mold and the inner side of the graphite crucible are set, and then a structural repair slurry is injected into the gap between the graphite crucible and the structural inner mold by means of boost injection to perform filling and repairing; When the damaged part of the graphite crucible is a through structure, a structural outer mold and a structural outer mold are set at the same time, and then the structural repair slurry is filled and repaired by pressurized injection on both sides of the graphite crucible at the same time.

9. The repair method for a graphite crucible according to claim 1, characterized in that: In step S3, the graphite crucible after grinding and polishing is directly subjected to coating forming, and the coating forming method is a plasma spraying method.